Undang-Undang Peternakan dan Kesehatan Hewan: Efektifitas dalam Pengendalian Penyakit Hewan Menular di Provinsi Lampung - Saswiyanti, Enny; Wulandari, Christine; Bakri, Samsul (Universitas Sang Bumi Ruwa Jurai, 2024)
Infectious animal diseases pose a serious threat to the health of animals and humans, as well as significant economic impacts. Law No. 41 of 2014 amending Law No. 19 of 2009 concerning Animal Husbandry and Animal Health regulates the security, assurance, utilization, and preservation of animals to ensure food sovereignty, independence, and security in order to achieve food sovereignty, independence, and security for the welfare and prosperity of the Indonesian people. The aim of this study is to analyze the effectiveness of the implementation of the Animal Husbandry and Animal Health Law and its derivatives in controlling infectious animal diseases in Lampung Province. The analysis results show that the implementation of the Animal Husbandry and Animal Health Law and its regulations has not been effective in protecting animal health, preventing disease, and its supervision processes have not been effective in preventing environmental contamination from the spread of infectious animal diseases in Lampung Province. This is evident from the entry and spread of animal diseases in Lampung Province such as Jembrana Disease, Foot and Mouth Disease (FMD), Lumpy Skin Disease (LSD), and African Swine Fever (ASF) in pigs